New Frontiers for Freedom - Canham, Erwin D. (New York Longmans, Green and Co., 1954)
New Frontiers for Freedom is a description of the American system in answer to Marxism. Erwin D. Canham, distinguished editor of the Christian Science Monitor, analyzes and presents the lessons national experience has taught us and presents our system of private voluntary organization and cooperation as a means of transmitting our meaning and cooperation to the world.
Keywords: United States -- Social conditions